The use of 4% hydroquinone, 0.1% tretinoin, and 0.1% betamethasone creams to prevent hyperpigmentation of split-thickness skin grafts in Long-Evans rats - Ozbey, Rafet; Okur, Mehmet Ihsan (Wiley, 2020)
Background The increase in the pigmentation of skin grafts during the healing process is a cosmetic problem. There are a variety of medical and surgical treatment options for skin graft darkening. Aims The aim of this study was to investigate the effects of topical hydroquinone, tretinoin, and betamethasone application on hyperpigmentation of skin grafts. Methods A skin defect was created on the backs of 17 Long-Evans rats, and a 2 x 2 cm split-thickness skin graft was sutured. After 15 days, eight rats in the treatment group were treated with application of hydroquinone, tretinoin, and betamethasone cream, while nine rats in the control group were not treated. Visual evaluation was performed on days 45 and 75 using the Melasma Severity Scale (MSS), and histological evaluation was performed on day 75 using S100 and Masson Fontana (MF) staining. The Mann-Whitney U test was used for statistical analysis. Results Mean MSS values of the treatment group on days 45 were significantly lower compared to the control group (P = .036). On day 75, the mean MSS score of the treatment group was also lower; however, the difference was not statistically significant (P = .302). Histological evaluation of S100 and MF staining scores of the treatment group showed fewer melanocytes and fewer pigments in epidermis (P = .009 and P = .002, respectively). Conclusions This study showed that topical application of hydroquinone, tretinoin, and betamethasone reduced the hyperpigmentation, number of melanocytes, and melanin pigment intensity that developed on the rat skin graft models. Clinical studies are needed to assess whether a similar effect could be observed with human skin grafts.
Keywords: hyperpigmentation; prevention; skin graft